Using of Matrix Laboratory (MATLAB) application in mathematics learning to increase students’ interest and understanding - Mushalli Rosalina Mushalli Rosalina (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
There are several computer application programs that can be used as a medium for learning physics, especially kinematics. One of them is the matrix laboratory software or better known as Matlab. Matlab is a software that can help us to perform mathematical calculations, data analysis, develop algorithms, perform simulations and modeling, and present them in graphical form. MatLab Matrix Laboratory mathematics software is a platform with a programming language created with the aim of being a tool for complex calculations or simulating a system that you want to simulate. This literature study aims to find out whether MatLab mathematics software as a learning medium can improve students' computing abilities through a review of related literature studies.